1995
DOI: 10.1029/94jc02497
|View full text |Cite
|
Sign up to set email alerts
|

Gulf Stream structure, transport, and recirculation near 68°W

Abstract: An analysis of the structure and transport of the Gulf Stream is undertaken using direct current meter observations from a 13-mooring array deployed near 68øW from June 1988 to August 1990. The analysis is based on a "stream-coordinate" approach, in which velocities are rotated into a local, downstream coordinate frame and averaged according to their relative cross-stream location within the current. The picture so obtained represents the average synoptic structure of the Gulf Stream, rather than the Eulerian-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
121
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(148 citation statements)
references
References 23 publications
25
121
2
Order By: Relevance
“…Positive relative vorticity is generated while the abyssal current passes under the stream, and after passing under the stream, the abyssal current immediately retroflects eastward onto the abyssal plain, thus eliminating the component of flow normal to the stream and preventing further southward abyssal current advection of the Gulf Stream pathway. As a result, specific features of the bottom topography and feedback from the influence of the Gulf Stream on the abyssal current pathway determined the latitude of the stream at 68.5-69" W. The speed and direction of the associated abyssal currents are consistent with those observed by Johns et al (1995).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Positive relative vorticity is generated while the abyssal current passes under the stream, and after passing under the stream, the abyssal current immediately retroflects eastward onto the abyssal plain, thus eliminating the component of flow normal to the stream and preventing further southward abyssal current advection of the Gulf Stream pathway. As a result, specific features of the bottom topography and feedback from the influence of the Gulf Stream on the abyssal current pathway determined the latitude of the stream at 68.5-69" W. The speed and direction of the associated abyssal currents are consistent with those observed by Johns et al (1995).…”
Section: Discussionsupporting
confidence: 75%
“…2 have mean maximum surface layer current speeds (see Table 2 in Section 3.4) in line with observations reported by Halkin and Rossby (1985), Joyce et al (1986). Johns et al (1995), and Schmitz (1996). Thus, differences in the separation pathway cannot be attributed to differences in the inertial character of the simulated currents.…”
Section: Impacts Of the Dwbc And The Eddy-driven Abyssal Circulation supporting
confidence: 76%
See 2 more Smart Citations
“…Similarly, the general expectation that waters constituting the upper limb of the MOC are carried continuously into the subpolar gyre via the Gulf Stream/ North Atlantic Current has come under some recent suspicion. Prior studies have shown that the Gulf Stream transports approximately 65 Sv (Sv [ 10 6 m 3 s 21 ) at Cape Hatteras (e.g., Johns et al 1995) and that about 20 Sv of this flow makes its way northward into the subpolar gyre via the North Atlantic Current. However, recent studies based on surface drifters show very little intergyre exchange in the North Atlantic, leaving open the question of how, where, or when the waters of the MOC upper limb enter the subpolar gyre to eventually return to their deep-water formation sites.…”
Section: Introductionmentioning
confidence: 99%